Understanding the role of substantive testing in audit fieldwork - Asman, Nur Asnani Amirah; Azis, Saflina; Mat, Mustafa Kamal (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Audited financial statements are essential for maintaining public confidence in capital markets and safeguarding the trust of investors, regulators, and the public, with regulatory oversight in Malaysia provided by bodies such as the Audit Oversight Board, Malaysian Institute of Accountants, and Malaysian Accounting Standards Board. However, the audit environment has become increasingly complex due to incomplete documentation, weak internal controls, and intentional misstatements arising from management pressure. These challenges underscore the importance of substantive testing in detecting material misstatements and ensuring credible audit opinions, although its effectiveness is often constrained by poor planning, time pressures, and limited auditor experience.